Particle swarm against market‐based optimisation for obstacle avoidance. Issue 22 (1st October 2013) - Palm, R.; Bouguerra, A.
Abstract : A comparison of particle swarm optimisation (PSO) and market‐based optimisation (MBO) is presented when applied to obstacle avoidance by mobile robots using artificial potential fields and special traffic rules. Most notably, PSO and MBO are applied to optimise the motion of mobile robots when acting in a common confined workspace. Simulation results show that both methods perform equally well with slight advantage for PSO.